ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK UMUM SYARIAH DENGAN BANK UMUM KONVENSIONAL DI INDONESIA - Yenni Annor Vivin; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe objectives of this research to make compare the finance performancebetween Islamic Commercial Banks and Conventional Commercial Banks inIndonesia in the period 2013-2016 by using financial ratios. Financial ratios areused consisting of CAR, NPL, LDR, BOPO, and ROA.The data used in this study were obtained from the Financial Statements ofCommercial Banks in 2013 to 2016, published by each Bank concerned. Afterpassing through the stage purposive sample, the sample is feasible to use as manyas four samples, two Islamic Commercial Banks, and 2 Conventional CommercialBank.Analytical techniques used to see comparison of financial performance ofIslamic Commercial Banks with Conventional Commercial Bank is the method ofIndependent sample t-test.The analysis showed that there are significant differences for each financial ratiobetween Islamic Commercial Banks and Conventional Commercial Banks inIndonesia. Islamic Commercial Banks has better performance in terms ofNPL,LDR, and BOPO ratios, while the Conventional Commercial Banks betterperformance in terms of the CAR, and ROA.Keywords : CAR, NPL, LDR, BOPO, ROA dan Independent sample t-test.